Spillovers and relationships in cross border banking: The case of Chile - Alegría, Andrés; Cowan, Kevin; García, Pablo (Journal of Financial Stability, 2018)
This paper assesses the spillovers from the global financial crisis on the cost and structure of cross-border funding of Chilean banks. To do so, it uses a novel dataset of individual lending operations between Chilean banks and their foreign counterparties between 2008 and 2016. The paper finds that global banks that experienced the largest hikes in their funding costs and were based in countries with large increases in sovereign risk increased spreads to Chilean banks most in this period, and that global financial turbulences also spilled through to the funding cost of Chilean banks. After the financial crisis of 2008 and 2009 the Chilean banking system underwent a significant change in its sources of funding, with a shift to new bank counterparties and a higher reliance on bond financing. The paper provides evidence that distance, as well as the intensity and age of banking relationships matter for the cost of cross border borrowing. Hence, this shift of sources of funding was initially a costly process. Over time as banking relationships developed with new counterparties, the cost of this shift decreased.